Green IoT for energy efficiency: Enabling technologies, challenges, and future research directions - Das, Resul; Adam, Iliyasu Yahaya; Öztop, Hakan Fehmi (Elsevier, 2025)
This study presents an overview of important aspects of the Green Internet of Things G-IoT with emphasis on fused G-IoT layered architecture, G-IoT enabling technologies, G-IoT opportunities, and applications, renewable energy-assisted Heating, ventilation, and air conditioning HVAC systems, as well as the challenges and research issues in green Internet of Things. The G-IoT is becoming a popular subject due to the evergrowing application of IoT systems. The Prevalence of G-IoT technology across society, industry, scientific institutions, and technology has led to billions of devices that work with the technology. However, this results in increased pollution, including increased carbon dioxide emissions, electronic waste, and excessive energy consumption. The need for eco-friendly and energy-efficient IoT systems necessitates the emergence of a G-IoT. This work discusses the fundamentals of G-IoT, issues, challenges, opportunities, and different applications with wide literature. Also, control of HVAC systems with G-IoT applications is studied. It is observed that there is a lack of sufficient research work on Green IoT at the application layer of IoT Architecture. The special need for incorporating renewable energy sources and local grids into HVAC systems for sustainability and to complement the trade-off between energy efficiency and building occupants' thermal comfort is being discussed. Finally, a framework for integrating local renewable grids with the main grid has been proposed to offload some HVAC energy consumption load.
Keywords: Green IoT; Renewable energy; Smart city; Cloud computing; Energy efficiency; Heating; ventilation; and air conditioning; HVAC